2020
DOI: 10.37190/ppmp/118475
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of vanadium and tungsten from spent selective catalytic reduction catalyst by alkaline pressure leaching

Abstract: Improving the efficiency of precious metal recovery from spent Selective Catalytic Reduction (SCR) catalyst provides economic benefits and promises sustainable use of resources. Here we demonstrate highly efficient alkaline pressure leaching method for the extraction of vanadium (V) and tungsten (W) from spent SCR catalyst. We analyzed the effects of experimental parameters such as the stirring speed, leaching agent concentration, leaching temperature, liquid-to-solid ratio, and leaching time. The Box-Behnken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…We found no significant differences in the prevalence of PTSD between men and women. Our results are, thus, not consistent with other findings in the general population and in other adult cohorts, which indicate that women are at increased risk for PTSD [22,[62][63][64][65][66][67], including during the COVID-19 pandemic [20]. Some studies suggest that women are at a higher risk of PTSD than men because of gender inequality and discrimination [68][69][70], genetic predisposition and hormonal influences, and individual gender roles [71].…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…We found no significant differences in the prevalence of PTSD between men and women. Our results are, thus, not consistent with other findings in the general population and in other adult cohorts, which indicate that women are at increased risk for PTSD [22,[62][63][64][65][66][67], including during the COVID-19 pandemic [20]. Some studies suggest that women are at a higher risk of PTSD than men because of gender inequality and discrimination [68][69][70], genetic predisposition and hormonal influences, and individual gender roles [71].…”
Section: Discussioncontrasting
confidence: 98%
“…Several studies have shown that pandemics, natural disasters, and other loss-of-life events are associated with increased PTSD among students [17][18][19][20]. Research among university students suggests that vicarious traumatization [21] via media coverage of COVID-19 [22,23] may have caused some cases of PTSD. In fact, a systematic review of general population studies found that there was more PTSD during the COVID-19 pandemic among young people than among the older population [20].…”
Section: Introductionmentioning
confidence: 99%
“…Spent SCR catalysts are increasingly generated from corresponding industrial sectors , and are gaining more attention given their very high concentration of strategic as well as base metals like vanadium, tungsten, and titanium . The spent SCR catalyst is subjected to recycling through an integrated hydrometallurgical route , to recover the valuable metal and simultaneously address the resulting global environmental issues …”
Section: Introductionmentioning
confidence: 99%
“…The use of a selective catalytic reduction (SCR) catalyst has become the most effective means of reducing nitrogen oxide (NO x ) emissions from stationary segments around the world because of strengthened regulatory trends and emerging environmental issues. The most widely used SCR catalyst, the V 2 O 5 –WO 3 /TiO 2 system, , contains a considerable amount of valuable metals (7–10 wt % of WO 3 , 0.5–1.5 wt % V 2 O 5 , and 70–80 wt % TiO 2 ) . This system shows excellent catalytic properties, such as a wide operating temperature window and high denitration rate …”
Section: Introductionmentioning
confidence: 99%
“…Alternately, alkali leaching (NaOH or Na2CO3) is widely used to process tungsten concentrates under high temperature and pressure conditions (Hairunnisha et al, 2007;Zhao et al, 2011;Liu et al, 2020). Na2CO3 is the most cited reactant in the literature (Paulino et al, 2012).…”
Section: Introductionmentioning
confidence: 99%